Enhancing Local Retribution as a Key Source of Local Revenue - Rachman, Ellys (Cendekiawan Indonesia Timur, 2024)
Retribution serves as a pivotal source of revenue for the State, distinguishing itself from taxes through the provision of a direct reciprocal value to the payer. In essence, individuals or entities paying retribution receive a tangible benefit or service in return, a concept fundamentally different from the general revenue-generating nature of taxes. This study adopts a descriptive qualitative approach to explore the dynamics of retribution and its impact on the revenue generation of Gorontalo City. Utilizing financial data specific to this locale, the research zeroes in on the local government of Gorontalo City as its primary sample, employing documentation methods to collect and analyze data. The analysis process encompasses verification, categorization, in-depth analysis, and meticulous organization of data to identify strategic issues and opportunities. The study further integrates SWOT analysis as a strategic tool to outline the current landscape and pinpoint areas for improvement. A key recommendation emerging from this research is the imperative for relevant local government units, specifically the Regional Work Unit (RWU), to enhance the management, supervision, and provision of guidance related to local retribution payments. By doing so, Gorontalo City can significantly improve the efficiency of its retribution collection processes, thereby fostering sustainable growth in local revenue streams. This comprehensive approach not only aims at optimizing current operations but also at securing long-term financial stability for the region through improved retribution management practices.